FORESTACIÓN CON CUATRO ESPECIES (Quercus coccifera L., Q.faginea Lam., Q. rotundifolia y Q. suber L.) DE FRONDOSAS EN EXTREMADURA P.M. (II Congreso Forestal Español, 1997)
The principal species of interest in order to form forests of mediterranean type (not of riverside) in the South half of the Iberian Peninsula are the genus Quercus L ones. In this work the outputs contrasted of development are introduced, 1 root and systems of protection utilized in a mixed afforestation with four species of the cited genus (Q. coccifera L., Q. faginea Lam., Q. rotundifolia Lam., Q. suber L.), in Extremadura (Spain). The analysis of the data offers different strategies in sylviculture for the forest recuperation of the zone in function of the species that utilize

Medicinal plants used in the Barros Area, Badajoz Province, Spain. (Journal of ethnopharmacology, 1997)
A study of the wild and cultivated medicinal plants used in the Barros Area (southern Spain) is reported, 48 plants distributed among 20 different families are used in the treatment of various human diseases. The use of Bellis annua L. Centaurea ornata Wild., Leuzea conifera (L.) DC., Pulicaria paludosa Link and Asparagus aphyllus L. is reported.
From Duplicate 2 (Medicinal plants used in the Barros Area, Badajoz Province, Spain. - Vázquez, F M; Suarez, M a; Pérez, A)

Relación entre la densidad de la masa y la producción de corcho en montes alcornocales del sur de españa (II Congreso Forestal Español, 1997)
In this paper the influence of cork-oak stand density on quantity and quality cork production is studied. Seventy five experimental plots were installed at Cortes de la Frontera (Málaga, Spain) cork-oak forests. Sorne stand and productive variables for different basal area were studied. The statistical analysis of the data permit to propose 20-25 m2!ha basal area as the optimum stand density

INFLUENCIA DE LA DENSIDAD DE LA MASA EN LA CALIDAD Y PRODUCCION DE CORCHO EN LOS ALCORNOCALES DE CORTES DE LA FRONTERA (MALAGA) (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
The influence of stand density on cork yield was evaluated for the Cortes de la Frontera (Spain) cork oak stand. Fifty five experimental plots were installed. The modular values of several variables which define cork oak yield potential of a tree, are presented by stand densitY'clusters (basal area groups). Likewise, many stand variables for different basal areas were studied

LIMITACIONES A LA REGENERACIÓN NATURAL DE LOS ALCORNOCALES EN EL PARQUE NACIONAL DE DOÑANA (HUELVA, ESPAÑA) P.M. (II Congreso Forestal Español, 1977)
The possible limitations to the in several experiences natural regeneration of the Quercus suber L. in a guarded area (Doñana) are undertaken in this study. The outputs offer a global vision of the natural regeneration in the Doñana's National Park. The production of seeds the sanitary state of the hoisted and their plagues, the attack of the spineless on the fruits and the climate don't harm the process of the natural regeneration in the -forest of Q. suber L. However the animal pressure (mammals), and the load cattle are the two factor s that impede the natural regeneration of the cork oak in Doñana. Finally, different strategies are contributed in order to recuperate the cork oak: fence, sowing, plantation and descent of the pressure animal in the zone.